Manajemen Pendidikan dan Pelatihan Kursus Gerakan Pramuka Universitas Islam Negeri Raden Mas Said Surakarta dalam Menyiapkan Pembina Pramuka - Riptono Riptono; Yusup Rohmadi; Hery Setiyatna (LPPM Institut Pendidikan Nusantara Global, 2026)
Basic Advanced Course (KMD) Training is a strategic program to equip students of the Elementary Madrasah Teacher Education Study Program (PGMI) at UIN Raden Mas Said Surakarta to be able to carry out dual roles as teachers and Scout leaders. This study aims to describe the management of KMD training which includes aspects of planning, implementation, evaluation, and certification. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that training planning is carried out systematically through cooperation between the university and the Branch Office, implementation prioritizes interactive andragogy methods, evaluation covers cognitive, affective, and psychomotor domains, and certification is national in nature and is an official requirement for Scout leaders. The conclusion of this study is that the management of KMD training has been implemented effectively and has a positive impact on improving the competence, leadership, and readiness of PGMI students as Scout leaders in the elementary education environment.